Internistische sportmedizinische Charakteristika des Frauenfußballs - Schneider, U.; Steuer, M.; Jakob, E. (Sport-Orthopädie - Sport-Traumatologie, 2011)
Women`s football is becoming increasingly popular both national and international. Exercise physiology characteristics describe increasingly conditional requirements. According to the amount of training and training intensity, cardiac adaptations can be observed. If higher workload is performed by top-class football players in additional international games, changes in the immune system are observed too. Due to this, adequate recovery time must be assured. In clinical daily routine the assessment of the iron metabolism is of great importance. Although the female athlete triad components (eating disorder, menstrual dysfunction and osteoporosis) occur less compared to other sports, attention should be paid to these characteristics in sports medicine examination.